The Influence of Slamet Riyadi Statue Games on Interactions with Peer Friends of Elementary School Students - Masesa, Adwi; Indrawan, Niko; Dyatmiko, Yusril Aryo; Sudinadji, Muhammad Bagus; Pratisti, Wiwien Dinar (Universitas Muhammadiyah Surakarta, 2019)
This research is done to know the presence of the influence of slamet riyadi statue games on interactions with peer friends of elementary school students. The independent variable in this research is slamet riyadi statue games. Whereas, dependent variable in this research is peer friends interactions. The design used in this research is Pre-Post Test One Group Design. The subject of this research is 207 V grade elementary school students and VI-grade in Surakarta. The flow of research used is subject given a pre-test using a scale for ± 10 minutes. Then a treatment of slamet riyadi statue games to the experiment group for ± 35 minutes. As long as the treatment goes, the researcher observed referring to the checklist observation sheet. The final flow is post-test using the same scale with pre-test however the number of items is random. The results of statistical analysis of research showed that there was no significant influence of slamet riyadi statue games on increasing the interactions among students. However, the results of descriptive analysis of data in this research, slamet riyadi statue games can increase the interaction among peer friends students in the category of less in total of 83%, fair 35%, and high 6%.